STAGNASI KEDUDUKAN DAN FUNGSI DEWAN PERWAKILAN DAERAH (DPD) DALAM PERATURAN PERUNDANG-UNDANGAN - Samaila, Fadilah (Universitas Tadulako, 2021)
This study raises the issue of:(1) whether the change in UU No.17 of 2014 into UU No.42 of 2014 and UU No.2 of 2018 concerning MD3 has an influence on the position and function of DPD.(2) whether the amendment of UU No.12 of 2011 to UU No.15 of 2019 concerning the formation of legislation affects the position and function of the DPD (3) what is the position and function of the DPD in an effort to strengthen through the fifth Amendment of the 1945 Constitution of the Republic of Indonesia. The objectives of this research are: (1) To find out about the change in UU No.17 of 2014 to UU 42 of 2014 and UU No.2 of 2018 concerning MD3 to influence the position and function DPD or not. (2) To find out about the amendment of UU No.12 of 2011 to UU No.15 of 2019 concerning the formation of laws and regulations influencing the position and function DPD or not. (3) To find legal concepts regarding the position and function of the DPD in an effort to strengthen through the fifth Amendment of the 1945 Constitution of the Republic of Indonesia. This research method uses a type of normative legal research using a statute approach and a conceptual approach, legal material collection techniques through library research, legal material analysis techniques are carried out in a qualitative juridical manner and the results are found in a descriptive form. The results of this study are: (1) UU No.42 of 2014 concerning changes to UU No. 17 of 2014 concerning MD3 and UU No. 2 of 2018 concerning the second amendment to UU No. 17 of 2014 concerning the MD3 in particular related to the authority of the DPD namely article 71, Article 249 paragraph (1) letter j, Article 250 paragraph (1), and Article 260 paragraph (1) in no way provide reinforcement to the position and function of the DPD.(2) UU No. 15 of 2019 concerning amendments to UU No. 12 of 2011 concerning the formation of legislation, specifically related to the authority of the DPD, namely Article 20, Article 71A, Article 95A, and Article 95B, no way provide a strengthening of the position and function of the DPD in the field of legislation, however, when viewed from the supervisory function, changes to the law provide reinforcement to DPD. (3) The position and function of the DPD in an effort to strengthen through the fifth Amendment of the 1945 Constitution of the Republic of Indonesia, which is equivalent to the DPR, that is, the right to submit, discuss and approve and reject the draft law in a particular field by amending Article 22D, Article 5 paragraph (1), Article 7A, Article 7C, and Article 20 paragraph (2). of course the format of the law must also change by placing the DPD in consideration weighing and remembering (if a bill originates from the DPD and the material is indeed related to the authority of the DPD)